Analysis Of The Obligation To Pay Vehicle Tax In The City Of Medan - Neiza Rizky Nuhajizah; Nayla Dwi Utami; Wilda Zulkarnain; Renny Maisyarah (Universitas Muhammadiyah Palu, 2026)
Motor Vehicle Tax (MVT) is one of the sources of Local Own-Source Revenue (PAD) that plays an important role in financing regional development. Medan City, as the center of economic activity in North Sumatra Province, has a high number of motor vehicles, resulting in considerable potential for MVT revenue. However, in practice, there are still problems in the form of tax arrears and suboptimal taxpayer compliance. This study aims to analyze the realization of motor vehicle tax revenue, the factors influencing taxpayer compliance, and the government’s efforts to improve motor vehicle tax compliance in Medan City. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation at the Medan City SAMSAT Office and from motor vehicle taxpayers. Data analysis was conducted qualitatively using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the realization of motor vehicle tax revenue at the Medan City SAMSAT has met and even exceeded the predetermined targets; however, its level of effectiveness is still categorized as moderately effective. Factors affecting taxpayer compliance include public awareness, economic conditions, transfer of vehicle ownership without name transfer, service quality, and lack of socialization. The government has implemented various measures, such as tax amnesty programs, e-Samsat digital service innovations, mobile Samsat services, public socialization, and law enforcement, to improve motor vehicle tax compliance.